School Culture in Shaping Religious Identity: A Critical Pedagogy Analysis of Islamic Early Childhood Education - Sekar Arum JQ; Mambaul Ngadimah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
The formation of religious identity in early childhood education requires an approach that transcends knowledge transfer toward continuous social construction. This study aims to analyze the role of school culture as a means of forming religious identity at RA Muslimat NU 093 Jonggol. A qualitative approach with a case study design was employed, with data collected through observation, semi-structured interviews, and documentation. Data were analyzed using the Miles, Huberman, and Saldana model, interpreted through Peter McLaren's Critical Pedagogy and Henri Tajfel's Social Identity Theory. Results indicate that religious identity is shaped through religious habituation, teacher role modeling, representation of Nahdlatul Ulama symbols and traditions, and social experiences fostering a sense of belonging to the religious community. Religious identity forms not through indoctrination but through ongoing social construction within school culture. These findings enrich scholarship on school culture in Islamic education from a religious identity construction perspective.